2021
DOI: 10.1371/journal.pone.0259621
|View full text |Cite
|
Sign up to set email alerts
|

Consent to minimally invasive tissue sampling procedures in children in Mozambique: A mixed-methods study

Abstract: Background Minimally invasive tissue sampling (MITS), also named minimally invasive autopsy is a post-mortem method shown to be an acceptable proxy of the complete diagnostic autopsy. MITS improves the knowledge of causes of death (CoD) in resource-limited settings. Its implementation requires understanding the components of acceptability, including facilitators and barriers in real-case scenarios. Methods We undertook a mixed-methods analysis comparing anticipated (hypothetical scenario) and experienced (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…In comparison, studies conducted with parents and family members of children who died and a MITS procedure was offered showed that the experienced acceptability was driven by the opportunity to prevent further deaths of children in the family. 9,10,12 Of note, this potential facilitator of anticipated acceptability of MITS in Quelimane is to some extent influenced by certain cultural norms, as the findings of our study revealed that some community members already practice a desire to know the COD following local practices, such as consultation with oracles through healers. This suggests that the introduction of MITS in this context could be in alignment with some of the existing practices surrounding the death of a child.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In comparison, studies conducted with parents and family members of children who died and a MITS procedure was offered showed that the experienced acceptability was driven by the opportunity to prevent further deaths of children in the family. 9,10,12 Of note, this potential facilitator of anticipated acceptability of MITS in Quelimane is to some extent influenced by certain cultural norms, as the findings of our study revealed that some community members already practice a desire to know the COD following local practices, such as consultation with oracles through healers. This suggests that the introduction of MITS in this context could be in alignment with some of the existing practices surrounding the death of a child.…”
Section: Discussionmentioning
confidence: 80%
“…4,7 This technique is being used in several contexts in LMICs and appears to be promising in terms of its greater acceptability because it is considered a fast, simple, and more user-friendly technique that can be performed by minimally trained staff, although there are factors considered to be important barriers that may put its acceptability at risk. [9][10][11] Existing evidence on the anticipated and experienced acceptability of the MITS procedure thus demonstrates the importance of recognizing the cultural mores and practices of the context where MITS is implemented. 9,12 Death and related post-mortem procedures are embedded in complex social, cultural, and religious environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the district of Quelimane was chosen because CISM has been conducting biomedical research there for 5 years, particularly on causes of deaths using minimally invasive tissue sampling (7). Currently, CISM is establishing an HDSS in the district.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…9 The Child Health and Mortality Prevention Surveillance (CHAMPS) Network was established in 2016 as a long-term collaborative platform to conduct standardized, comprehensive, and highquality surveillance for causes of child mortality (including stillbirths) in high-mortality, sentinel sites in sub-Saharan Africa and Asia. 10 Core surveillance activities include the use of the innovative postmortem minimally invasive tissue sampling (MITS) approach for COD investigation, 11 which is more reliable than verbal autopsy and clinical records investigation 7,12 and more socially and culturally acceptable than complete diagnostic autopsies. 13 The accumulation of cases from CHAMPS sentinel sites is providing a more robust backbone to support future child mortality statistics.…”
Section: Introductionmentioning
confidence: 99%